Peran Pembelajaran Berbasis Proyek pada Materi Sistem Pernapasan dalam Memantik Kreativitas Siswa Sekolah Dasar - Nur Aliyah; Ibnu Muthi (Edukasi Elita : Jurnal Inovasi Pendidikan, 2025)
This study aims to examine the role of Project-Based Learning (PjBL) in fostering creativity among elementary school students, particularly in the respiratory system topic within Natural Science (IPA) learning. Creativity, as one of the essential 21st-century competencies, needs to be developed from an early age through learning approaches that are active, contextual, and student-centered. This research employs a qualitative method with a library research approach, utilizing various sources such as accredited scientific journal articles, relevant books, and previous research reports published between 2017 and 2025. Data were analyzed using the Miles and Huberman model, which consists of data reduction, data display, and conclusion drawing. The results show that the implementation of PjBL in the respiratory system topic effectively enhances student creativity through exploratory activities such as creating lung models, organizing clean air campaigns, and conducting simple experiments. PjBL also supports the development of collaborative skills, problem-solving abilities, and learning responsibility. In conclusion, PjBL is an effective and relevant instructional strategy to increase creativity and create meaningful learning experiences at the elementary school level, especially in science education.